Comparison of an optimized electrical variable transmission with the Toyota Hybrid System. (15th November 2020) - Verbelen, Florian; Lhomme, Walter; Vinot, Emmanuel; Stuyts, Jeroen; Vafaeipour, Majid; Hegazy, Omar; Stockman, Kurt; Sergeant, Peter
Abstract: This paper discusses the comparison of two series–parallel hybrid electrical vehicles. The first one is based on the Toyota hybrid system, while the second one is equipped with an electrical variable transmission. The problem with previous comparisons between these two transmissions is the lack of validated data used to support the comparison as well as a comprehensive study on the sizing of the electrical variable transmission for a given vehicle and load cycle. To tackle these issues, a validated model of an electrical variable transmission is used in combination with validated scaling laws to assess design changes. This scalable model is used to determine the optimal design and the impact of sizing on the fuel consumption of the vehicle. To exclude the impact of the chosen control methodology, dynamic programming has been used. This technique is not only used to optimize the operating points of the internal combustion engine, but also to find the optimal DC-bus voltage in order to optimize the system level efficiency. The comparison is performed for multiple driving cycles that all show the added value of the electrical variable transmission based hybrid electrical vehicle. On average, over the different driving cycles, a reduction in fuel consumption of 4.75% is achieved while using an electrical variable transmission. Highlights: Detailed comparison between two series–parallel hybrid electrical vehicles. Optimized energy management based on dynamic programming. Validated scaling laws to ensure a fair comparison in terms of sizing. The electrical variable transmission outperforms Toyota hybrid system. The electrical variable transmission reduces fuel consumption by 4.75%.